Influence of the Arctic Oscillation on the variability of winter mean temperatures in Libya (Journal of Libya for geographical studies, 2021)
The Arctic Oscillation (AO) effects the climate of the northernhemisphere. Several previous studies have been shown the effectof the Arctic Oscillation (AO) on climate conditions in winter inAmerica, Europe, Asia and the Mediterranean region; Therefore,this study attempts to investigate the effect of the ArcticOscillation (AO) on the mean temperature, As well as the meanmaximum and minimum winter temperatures in Libya (December-January-February) by analyzing the correlation for 11 stations over50 years (1961-2010) and testing it statistically. It was found thatthe results of the temperature relationship of the winter months arenegatively related between the Arctic Oscillation (AO) and all themean temperatures for the winter months in all the study stations,The study also revealed that the mean January temperature is lesscorrelated with the AO index than the months of December andFebruary. The results also indicate that there is a clear spatialdiscrepancy with significant statistical significance P-value lessthan (0.05) between the correlation of the AO index and the meanwinter temperature in the west, east and south of the country.Among the results is also that the AO values started to decreasegradually starting from 1991-2010 in all winter months(December-January-February). Which led to the tendency of themean winter temperature to rise, based on the inverse relationshipof the correlation.
Keywords: Arctic Oscillation; AO; winter season; Libya